Surgical treatment of burns : Special aspects of pediatric burns - Bührer, Gregor; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas (Hautarzt, 2017)
BACKGROUND: Treatment of pediatric burn patients is very important because of the sheer frequency of burn wounds and the possible long-term ramifications. Extensive burns need special care and are treated in specialized burn centers. OBJECTIVES: The goal of this work is to present current standards in burn therapy and important innovations in the treatment of burns in children so that the common and small area burn wounds and scalds in pediatric patients in day-to-day dermatological practice can be adequately treated. MATERIALS AND METHODS: Analysis of current literature, discussion of reviews, incorporation of current guidelines. RESULTS: Burns in pediatric patients are common. Improvement of survival can be achieved by treatment in burn centers. The assessment of burn depth and area is an important factor for proper treatment. We give an overview for outpatient treatment of partial thickness burns. New methods may result in better long-term outcome. CONCLUSIONS: Adequate treatment of burn injuries considering current literature and guidelines improves patient outcome. Rational implementation of new methods is recommended.
EVALuna2:32844